Learning from the early adopters: developing the digital practitioner - Liz Bennett (Association for Learning Technology, 2014)
This paper explores how Sharpe and Beetham's Digital Literacies Framework which was derived to model students' digital literacies, can be applied to lecturers' digital literacy practices. Data from a small-scale phenomenological study of higher education lecturers who used Web 2.0 in their teaching and learning practices are used to examine if this pyramid model represents their motivations for adopting technology-enhanced learning in their pedagogic practices. The paper argues that whilst Sharpe and Beetham's model has utility in many regards, these lecturers were mainly motivated by the desire to achieve their pedagogic goals rather than by a desire to become a digital practitioner.